Skuteczność kompleksowej fizjoterapii ambulatoryjnej u chorych z rozpoznaniem zapalenia nadkłykcia bocznego kości ramiennej = The efficiency of complex outpatient physiotherapy in patients diagnosed with lateral epicondylitis - Pasiud, Klaudia; Garczyński, Wojciech (Journal of Education, Health and Sport, 2016)
Pasiud Klaudia, Garczyński Wojciech. Skuteczność kompleksowej fizjoterapii ambulatoryjnej u chorych z rozpoznaniem zapalenia nadkłykcia bocznego kości ramiennej = The efficiency of complex outpatient physiotherapy in patients diagnosed with lateral epicondylitis. Journal of Education, Health and Sport. 2016;6(8):400-416. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60741 http://ojs.ukw.edu.pl/index.php/johs/article/view/3764 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016. Skuteczność kompleksowej fizjoterapii ambulatoryjnej u chorych z rozpoznaniem zapalenia nadkłykcia bocznego kości ramiennej The efficiency of complex outpatient physiotherapy in patients diagnosed with lateral epicondylitis Klaudia Pasiud1, A, B, D-F, Wojciech Garczyński2, 3, A, C-F 1absolwentka Wydziału Zamiejscowego w Szczecinie, Wyższej Szkoły Edukacji i Terapii w Poznaniu 2Wyższa Szkoła Edukacji i Terapii w Poznaniu, Wydział Studiów Edukacyjnych 3Indywidualna Praktyka Fizjoterapeutyczna w Szczecinie A. przygotowanie projektu badawczego; B. zbieranie danych; C. analiza statystyczna; D. interpretacja danych; E. przygotowanie manuskryptu; F. opracowanie piśmiennictwa; G. pozyskanie funduszy. Autor do korespondencji: dr n. o zdr. Wojciech Garczyński Indywidualna Praktyka Fizjoterapeutyczna ul. Biskupa Bandurskiego 71/17 71-685 Szczecin mail: w.garczynski@gmail.com STRESZCZENIE WSTĘP. Zapalenie nadkłykcia bocznego kości ramiennej, zwane powszechnie „łokciem tenisisty” jest jedną z najczęściej rozpoznawanych dolegliwości w okolicy stawu łokciowego u osób między 30 a 65 rokiem życia. Schorzenie to występuje wśród 1-3% populacji, a jej główną przyczyną są przeciążenia mięśni prostowników przedramienia w wyniku długotrwałej pracy dynamicznej lub statycznej o niewielkim obciążeniu. Osoby, które zawodowo wykonują czynności manualne są szczególnie predysponowane do powstania tego schorzenia. CEL. Celem przeprowadzonych badań była ocena skuteczności kompleksowej fizjoterapii u pacjentów z rozpoznaniem zapalenia nadkłycia bocznego kości ramiennej. MATERIAŁ I METODY. Badanie przeprowadzono w grupie 40 osób (25 mężczyzn i 15 kobiet) z rozpoznaniem zapalenia nadkłycia bocznego kości ramiennej, u których dolegliwości bólowe utrzymywały się od 4 do 6 miesięcy. Średni wiek grupy badanej to 44 lata ± 10,22. W badaniu wykorzystano metodę sondażu diagnostycznego w oparciu o autorski kwestionariusz ankiety oraz standaryzowany kwestionariusz dotyczący niesprawności kończyny górnej DASH (Disability of the Arm, Shoulder and Hand). Poziom dolegliwości bólowych oceniono za pomocą skali NRS (Numerical Rating Scale). Ponadto u badanych wykonano trzy testy funkcjonalne: test Thomsona, test Cozena i test Milla. Do analizy wyników wykorzystano arkusz kalkulacyjny Excel i program Statistica 12. WYNIKI. Najczęściej zlecanymi zabiegami fizjoterapeutycznymi w przypadku zapalenia nadkłycia bocznego kości ramiennej były: laseroterapia (67,5%), krioterapia (60%) oraz ultradźwięki (55%). Zaobserwowano istotną statystycznie różnicę (p<0,001) w poziomie dolegliwości bólowych przed (6,67) i po serii zabiegów (2,27) w skali NRS oraz w poziomie niesprawności kończyny górnej w skali DASH (przed 58,49, po serii zabiegów 23,90). W testach funkcjonalnych uzyskano poprawę u prawie 95% badanych. WNIOSKI. Kompleksowa fizjoterapia, obejmująca od 3 do 5 zabiegów, prowadzona w ramach fizjoterapii ambulatoryjnej, jest skuteczna u pacjentów z rozpoznaniem zapalenia nadkłykcia bocznego kości ramiennej. SŁOWA KLUCZOWE: kompleksowa fizjoterapia, fizjoterapia ambulatoryjna, łokieć tenisisty. SUMMARY INTRODUCTION. Lateral epicondylitis commonly known as 'tennis elbow' is one of the most often diagnosed problems in the neighbourhood of the elbow joint in patients aged 30 to 65. The disease is present among 1-3% of the population and its main cause is the overload of the forearm extensor muscles as a result of long-term dynamic work or static work of small load. The people who perform manual activities professionally are especially predisposed to the disease. PURPOSE. The purpose of the study carried out was the evaluation of the efficiency of complex physiotherapy in patients diagnosed with lateral epicondylitis. MATERIAL AND METHODS. The study was carried out in a group of 40 people (25 men and 15 women) diagnosed with lateral epicondylitis who have experienced pain for 4 to 6 months. The average age of the study group was 44 years ± 10.22. In the study the method of diagnostic survey was applied based on the author's questionnaire and standardized questionnaire concerning the disability of the upper limb, DASH (Disability of the Arm, Shoulder and Hand). Pain level was assessed by means of NRS (Numerical Rating Scale). Moreover, there were three functional tests performed on the interviewees: Thomson's test, Cozen's test and Mill's test. Excel spreadsheet and Statistics 12 programme were used for the purposes of the analysis of the results. RESULTS. The physiotherapeutic procedures ordered most often for lateral epicondylitis were: laser therapy (67.5%), cryotherapy (60%) and ultrasounds (55%). Statistically significant different was observed (p<0.001) with regard to the pain level before (6.67) and after a series of procedures (2.27) in the NRS as well as with regard to the level of the upper limb disability in the DASH scale (58.49 before and 23.90 after a series of procedures). Improvement was observed in almost 95% of the interviewees in the functional tests. CONCLUSIONS. Complex physiotherapy covering 3 to 5 procedures performed in terms of outpatient physiotherapy is efficient in patients diagnosed with lateral epicondylitis. KEY WORDS: complex physiotherapy, outpatient physiotherapy, tennis elbow.